5(x+9)=8(x-6)

Simple and best practice solution for 5(x+9)=8(x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+9)=8(x-6) equation:


Simplifying
5(x + 9) = 8(x + -6)

Reorder the terms:
5(9 + x) = 8(x + -6)
(9 * 5 + x * 5) = 8(x + -6)
(45 + 5x) = 8(x + -6)

Reorder the terms:
45 + 5x = 8(-6 + x)
45 + 5x = (-6 * 8 + x * 8)
45 + 5x = (-48 + 8x)

Solving
45 + 5x = -48 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
45 + 5x + -8x = -48 + 8x + -8x

Combine like terms: 5x + -8x = -3x
45 + -3x = -48 + 8x + -8x

Combine like terms: 8x + -8x = 0
45 + -3x = -48 + 0
45 + -3x = -48

Add '-45' to each side of the equation.
45 + -45 + -3x = -48 + -45

Combine like terms: 45 + -45 = 0
0 + -3x = -48 + -45
-3x = -48 + -45

Combine like terms: -48 + -45 = -93
-3x = -93

Divide each side by '-3'.
x = 31

Simplifying
x = 31

See similar equations:

| |x|= | | 36x+2=110 | | 5t-whent=-4 | | 139=17x+3 | | 141/2?= | | -2cos^2x-5cos+3=0 | | 141/2= | | 4(3x+6)=15x-8+4x | | 5y+4=5y+5 | | -x/3=1/8 | | 6m-3=27 | | n+20when*n=5 | | -24=7x+(-3) | | 8(6v-5)-2v=-132 | | h=16t^2+20t+4 | | 2(t+18)=-3(2-t) | | -(-2p+7)+4(1+3p)= | | 5*(0.06/0.03) | | -6u-2=-8(u-1) | | -8/7a=32 | | -x+7-4x=19-5x | | -4(t+2)=28 | | (4x+10)+8x= | | 4-3/(x^2) | | 4x^2-7x-j=0 | | 3(-2-6)= | | 49-14=5(x-6) | | (2u-5)(6+u)=0 | | x+24+4x=-22-4x-26 | | -1/4x=21/4 | | (15x+7y)+(48x+25y)= | | 7-3(x-1)=2x |

Equations solver categories